Net zero emission buildings: next generation of benchmarks and calculation rules. Issue 1 (1st September 2022) - Balouktsi, M; Lützkendorf, T
Abstract: The definition of ambitious life cycle-based benchmarks and target values to limit the GHG emissions of buildings is seen as one of the most important steps in pushing the construction and real estate sector in significantly reducing its contribution to global warming. Especially target values are no longer only developed from a bottom-up perspective. There is now an interest by governments and sustainability assessment system providers in supplementing bottom-up approaches with science-based top-down approaches as part of their responsibility to respect planetary boundaries. The creation of GHG emission budgets in combination with target values, as well as the introduction of strict enough legal binding requirements already today is critical for achieving a climate-neutral building stock. Achieving these tasks requires tackling still open methodological issues. Following the work of IEA EBC Annex 72 and current developments in Germany, the paper presents main questions, key steps, modelling aspects that can cause variation and uncertainties, as well as clarifies key terms and definitions. It is highlighted that although a net zero emission requirement is a universal benchmark, information on system boundaries and calculation rules are still necessary to provide evidence of its fulfilment.